ALAT PENDETEKSI KEBOCORAN GAS LPG(LIQUIFIED PETROLEUM GAS) BERBASIS ARDUINO UNO - Muhamad Muhtar; Lilik Ariyanto; Arif Wibisono (Universitas PGRI Semarang, 2021)
Abstract- This research is motivated by the many cases of LPG (Liquified Petroleum Gas) leakage which resulted in more fatal losses and often claimed lives. Therefore, the researcher made a study that resulted in a product in the form of an LPG gas detector that can be used in the household scope. So that the user gets more security in the use of LPG gas considering that the need for LPG gas is a basic need of the community. This research uses the R&D (Research and development) method with the waterfall pressman development model which produces a physical device based on the Arduino Uno type microcontroller where the tool will work automatically to provide a warning and early handling in the form of sound and fan motion so that the leaking LPG gas can come out. room. Before conducting the research, the researcher conducted an expert validation test aimed at assessing the feasibility of the tool for research. The results of this study were obtained through giving questionnaires to respondents using LPG gas which were then processed. The average percentage of this research is 97.5% which is then converted into a qualitative form, which is strongly agree. So that this research can be known reliable for use.